Excess costs of type 2 diabetes and their sociodemographic and clinical determinants: a cross-sectional study using data from the German Health Interview and Examination Survey for Adults (DEGS1) - Hans-Helmut König; Christian Schmidt; Jens Baumert; Christian Brettschneider; Alexander Konnopka; Hannah König; A Rommel (BMJ Open)
Objectives The objectives of this study were to estimate the direct and indirect excess costs of type 2 diabetes mellitus (T2D) using data representative for the German adult population and to investigate the association of sociodemographic and clinical determinants with these excess costs.Setting We calculated mean annual costs for individuals with T2D and a control group without diabetes, using data on healthcare utilisation and productivity losses from the cross-sectional German Health Interview and Examination Survey for Adults. We adjusted for group differences using entropy balancing and estimated excess costs for total, direct, indirect costs and additional cost categories using generalised linear models. We performed subgroup analyses to investigate the association of sociodemographic (age, sex and education) and clinical determinants (diabetes duration, glycaemic index and complications) with excess costs.Participants The final study sample included n=325 individuals with T2D and n=4490 individuals without diabetes in the age between 18 and 79 years.Results Total excess costs amounted to €927, of which €719 were attributable to direct and €209 to indirect excess costs. Total costs were significantly increased by 28% for T2D compared with controls. Group differences in direct, outpatient and medication costs were statistically significant. Medication costs were 88% higher for T2D and had the highest share in direct excess costs. With respect to specific determinants, direct excess costs ranged from €203 for 4–10 years diabetes duration to €1405 for diabetes complications. Indirect excess costs ranged from €−544 for >10 years diabetes duration to €995 for high education.Conclusions T2D was associated with high costs, mainly due to direct costs. As pointed out by our results, diabetes complications and comorbidities have a large impact on the costs, leaving medication costs as main contributor of T2D excess costs.